Discover answers to your questions with Westonci.ca, the leading Q&A platform that connects you with knowledgeable experts. Get quick and reliable solutions to your questions from knowledgeable professionals on our comprehensive Q&A platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
To determine the sum of the complex numbers [tex]\( z_1 \)[/tex] and [tex]\( z_2 \)[/tex], follow these steps:
Given:
[tex]\[ z_1 = 2 + \sqrt{3} i \][/tex]
[tex]\[ z_2 = 1 - \sqrt{3} i \][/tex]
Step 1: Write down the formula for the sum of two complex numbers.
[tex]\[ z_{\text{sum}} = z_1 + z_2 \][/tex]
Step 2: Substitute the given values into the sum formula.
[tex]\[ z_{\text{sum}} = (2 + \sqrt{3} i) + (1 - \sqrt{3} i) \][/tex]
Step 3: Combine the real parts of [tex]\( z_1 \)[/tex] and [tex]\( z_2 \)[/tex]:
[tex]\[ \text{Real part of } z_{\text{sum}} = 2 + 1 = 3 \][/tex]
Step 4: Combine the imaginary parts of [tex]\( z_1 \)[/tex] and [tex]\( z_2 \)[/tex]:
[tex]\[ \text{Imaginary part of } z_{\text{sum}} = (\sqrt{3}) i - (\sqrt{3}) i = 0 i \][/tex]
Step 5: Combine the real and imaginary parts to write the final result:
[tex]\[ z_{\text{sum}} = 3 + 0 i = 3 \][/tex]
Thus, the sum of [tex]\( z_1 \)[/tex] and [tex]\( z_2 \)[/tex] is [tex]\( 3 \)[/tex].
So, the correct answer is:
[tex]\[ \boxed{3} \][/tex]
Given:
[tex]\[ z_1 = 2 + \sqrt{3} i \][/tex]
[tex]\[ z_2 = 1 - \sqrt{3} i \][/tex]
Step 1: Write down the formula for the sum of two complex numbers.
[tex]\[ z_{\text{sum}} = z_1 + z_2 \][/tex]
Step 2: Substitute the given values into the sum formula.
[tex]\[ z_{\text{sum}} = (2 + \sqrt{3} i) + (1 - \sqrt{3} i) \][/tex]
Step 3: Combine the real parts of [tex]\( z_1 \)[/tex] and [tex]\( z_2 \)[/tex]:
[tex]\[ \text{Real part of } z_{\text{sum}} = 2 + 1 = 3 \][/tex]
Step 4: Combine the imaginary parts of [tex]\( z_1 \)[/tex] and [tex]\( z_2 \)[/tex]:
[tex]\[ \text{Imaginary part of } z_{\text{sum}} = (\sqrt{3}) i - (\sqrt{3}) i = 0 i \][/tex]
Step 5: Combine the real and imaginary parts to write the final result:
[tex]\[ z_{\text{sum}} = 3 + 0 i = 3 \][/tex]
Thus, the sum of [tex]\( z_1 \)[/tex] and [tex]\( z_2 \)[/tex] is [tex]\( 3 \)[/tex].
So, the correct answer is:
[tex]\[ \boxed{3} \][/tex]
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.